1975
DOI: 10.1093/infdis/131.supplement.s81
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Clostridium in Human Infections: Evaluation of 114 Cases

Abstract: One hundred fifty-two strains of Clostridium were isolated from 144 patients over a 14-month-peroid. These included 23 recognized species and 23 strains that were unclassified. Soft tissues or abscesses yielded 84 strains of Clostridium. Intraabdominal sites predominated, but clostridia were recovered from empyema, carcinoma, frostbite with gas gangrene, muscle abscess, aortic graft, and brain abscess. Blood cultures yielded 65 strains of Clostridium from 49 patients, representing 0.3% of 16,314 blood cultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
77
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(81 citation statements)
references
References 11 publications
1
77
0
Order By: Relevance
“…Early studies showed a direct correlation between increased abundance of Bacteroides sp., Streptococcus gallolyticus (formerly S. bovis), and Clostridium sp in CRC patients. [24][25][26] More recently, microbiome studies using next-generation sequencing approaches have shown that a decrease in bacterial diversity in the gut microbiota was associated with higher CRC risk in stool samples. 21 Moreover, CRC patients have a distinct gut bacterial community composition with increased abundance of Fusobacterium, Porphyromonas (which have been related to inflammation 21,27,28 ), Coriobacteridae and Roseburia 29 and decreased abundance of Firmicutes, specifically Clostridia (involved in fermentation of dietary fiber 30 ) and Enterobacteriaceae 29 in both stool and mucosal samples.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies showed a direct correlation between increased abundance of Bacteroides sp., Streptococcus gallolyticus (formerly S. bovis), and Clostridium sp in CRC patients. [24][25][26] More recently, microbiome studies using next-generation sequencing approaches have shown that a decrease in bacterial diversity in the gut microbiota was associated with higher CRC risk in stool samples. 21 Moreover, CRC patients have a distinct gut bacterial community composition with increased abundance of Fusobacterium, Porphyromonas (which have been related to inflammation 21,27,28 ), Coriobacteridae and Roseburia 29 and decreased abundance of Firmicutes, specifically Clostridia (involved in fermentation of dietary fiber 30 ) and Enterobacteriaceae 29 in both stool and mucosal samples.…”
Section: Introductionmentioning
confidence: 99%
“…However, subsequent investigations of this issue have failed to confirm these observations (90,186,199). The etiologic agent C. difficile has been isolated infrequently from other human sources (109,110,250 (15,104,163,170,171,254,260,261,271). The enterotoxin was found to be 100-to 1,000-fold less cytotoxic than the cytotoxin and demonstrated a fluid response when tested in ligated ileal loops.…”
Section: Introductionmentioning
confidence: 99%
“…Clostridium subterminale (C subterminale) is one of the Clostridium species most frequently isolated from the soil. To the best of our knowledge, only three cases of infection due to C. subterminale (one case of pleuropulmonary infection and the other two consisting of soft tissue infections) have been reported in adults in the English-language medical literature (2,3). This is the first reported case of septicemia due to C. subterminale.…”
mentioning
confidence: 87%